Bimbingan dan Konseling Belajar Berbasis Project-Based Learning dan Case Method - Suciani Latif; Akhmad Harum; Akbar Na’im Fadhlillah (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2026)
This study aims to develop a learning guidance and counseling textbook based on Project-Based Learning (PjBL) and Case Method. The study employed a Research and Development approach using the ADDIE model, focusing on the development and evaluation stages. The product consists of a 23-chapter textbook integrating theoretical foundations, practical guidance, authentic projects, case analysis, student worksheets, and digital learning support. Product practicality was evaluated through expert judgment and student responses. The results showed that the textbook was categorized as very practical, with an expert assessment score of 91.0% and student responses of 86.6%. These findings indicate that the developed textbook is relevant, easy to use, and supports active learning in guidance and counseling education. The study highlights the importance of structured teaching materials that integrate project-based and case-based learning approaches.